Workshop Matematika Kreatif: Strategi Menyelesaikan Soal Cerita untuk Siswa SD Negeri 4 Dobo: Creative Mathematics Workshop: Strategies for Solving Word Problems for Students of SD Negeri 4 Dobo - Moh. Erwin Budiana; Mukh Khusnaini; Karten Halirat; Chrismanto Purba; Hizkia Gymnastic Mautang; Sumarah Suryaningrum (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kemampuan berpikir kritis dan kreatif siswa dalam menyelesaikan soal cerita matematika melalui pendekatan yang menyenangkan. Hal tersebut di dasari banyak siswa SD Negeri 4 Dobo mengalami kesulitan memahami dan menyelesaikan soal cerita matematika, sehingga dibutuhkan strategi kreatif untuk meningkatkan pemahaman dan minat belajar mereka.. Metode yang digunakan meliputi permainan matematika, diskusi kelompok, dan latihan soal yang dikemas secara kreatif agar siswa lebih mudah memahami konsep serta strategi penyelesaian soal cerita. Hasil kegiatan menunjukkan peningkatan pemahaman siswa terhadap langkah-langkah penyelesaian soal cerita, kemampuan analisis masalah, dan minat belajar matematika. Workshop ini diharapkan dapat menjadi model pembelajaran inovatif yang mendukung pengembangan kemampuan problem solving siswa sekolah dasar. Kata Kunci: Matematika Kreatif, Soal Cerita, SD Negeri 04 Dobo Abstract This community service activity aims to improve students’ critical and creative thinking skills in solving mathematical word problems through an engaging and enjoyable approach. This initiative is based on the fact that many students at SD Negeri 4 Dobo experience difficulties in understanding and solving mathematical word problems, indicating the need for creative strategies to enhance their comprehension and learning interest. The methods used include mathematical games, group discussions, and practice exercises designed creatively so that students can more easily understand concepts and problem-solving strategies. The results of the activity show an improvement in students’ understanding of the steps involved in solving word problems, their problem analysis skills, and their interest in learning mathematics. This workshop is expected to serve as an innovative learning model that supports the development of problem-solving skills among elementary school students Keywords: Creative Mathematics, Word Problems, SD Negeri 04 Dobo